An evaluation of the implementation of maternal obesity pathways of care: a mixed methods study with data integration. - Nicola Heslehurst; Sarah Dinsdale; Gillian Sedgewick; Helen Simpson; Seema Sen; Carolyn Dawn Summerbell; Judith Rankin (PLoS ONE)
Objectives Maternal obesity has multiple associated risks and requires substantial intervention. This research evaluated the implementation of maternal obesity care pathways from multiple stakeholder perspectives. Study design A simultaneous mixed methods model with data integration was used. Three component studies were given equal priority. 1: Semi-structured qualitative interviews explored obese pregnant women's experiences of being on the pathways. 2: A quantitative and qualitative postal survey explored healthcare professionals' experiences of delivering the pathways. 3: A case note audit quantitatively assessed pathway compliance. Data were integrated using following a thread and convergence coding matrix methods to search for agreement and disagreement between studies. Results Study 1: Four themes were identified: women's overall (positive and negative) views of the pathways; knowledge and understanding of the pathways; views on clinical and weight management advice and support; and views on the information leaflet. Key results included positive views of receiving additional clinical care, negative experiences of risk communication, and weight management support was considered a priority. Study 2: Healthcare professionals felt the pathways were worthwhile, facilitated good practice, and increased confidence. Training was consistently identified as being required. Healthcare professionals predominantly focussed on women's response to sensitive obesity communication. Study 3: There was good compliance with antenatal clinical interventions. However, there was poor compliance with public health and postnatal interventions. There were some strong areas of agreement between component studies which can inform future development of the pathways. However, disagreement between studies included a lack of shared priorities between healthcare professionals and women, different perspectives on communication issues, and different perspectives on women's prioritisation of weight management. Conclusion The differences between healthcare professionals' and women's priorities and perspectives are important factors to consider when developing care pathways. Shared perspectives could help facilitate more effective implementation of the pathway interventions that have poor compliance.